The Role of Local Government in the Creation of Innovation in Regional Peripheral Economies (A Case Study of The Lublin Region, Poland) - Adamowicz, Mieczysław; Zwolińska-Ligaj, Magdalena (Olsztyn Economic Journal, 2018)
The subject of this work is to find ways to strengthen the innovativeness of economies in local systems, both from government authorities and business entities. The aim of the study is to assess the scale and scope of activities undertaken by the examined local government units aimed at strengthening the innovativeness of local economies. The paper presents the perspective of local government and enterprises, which allowed for a positive verification of the hypothesis of the existing inconsistency between the activity of government authorities and the expectations of entrepreneurs in support of their pro-innovation activities by local governments. The paper demonstrates that activities aimed at creating innovative conditions have been undertaken on a small and limited scale by local authorities. Nevertheless, local authorities are aware of the need to intensify activities that are particularly important for the local economic sector. The empirical part of this work was based on the results of a survey conducted in 2015, using an interview questionnaire addressed to representatives of local authorities and enterprises in two counties of the Lubelskie Province. The research material consisted of 14 interviews with representatives of municipalities and 147 interviews with entrepreneurs.